2014
DOI: 10.1021/bm401776z
|View full text |Cite
|
Sign up to set email alerts
|

N-Terminal Protein Tails Act as Aggregation Protective Entropic Bristles: The SUMO Case

Abstract: The formation of β-sheet enriched amyloid fibrils constitutes the hallmark of many diseases but is also an intrinsic property of polypeptide chains in general, because the formation of compact globular proteins comes at the expense of an inherent sequential aggregation propensity. In this context, identification of strategies that enable proteins to remain functional and soluble in the cell has become a central issue in chemical biology. We show here, using human SUMO proteins as a model system, that the recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…It may also affect the aggregation properties of target proteins. An alternative mechanism that has been proposed is that SUMO directly affects inter- or intramolecular interactions of target proteins (Graña-Montes et al, 2014; Sabate et al, 2012). As mentioned above, our bioinformatics analysis has not as yet located a putative SUMO-interacting motif in the protein sequence of CPEB3, thereby excluding a direct interaction of SUMO and CPEB3.…”
Section: Discussionmentioning
confidence: 99%
“…It may also affect the aggregation properties of target proteins. An alternative mechanism that has been proposed is that SUMO directly affects inter- or intramolecular interactions of target proteins (Graña-Montes et al, 2014; Sabate et al, 2012). As mentioned above, our bioinformatics analysis has not as yet located a putative SUMO-interacting motif in the protein sequence of CPEB3, thereby excluding a direct interaction of SUMO and CPEB3.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregation constraints the evolution of proteins and accordingly nature have evolved different strategies to minimize protein aggregation in sequences and structures. Essentially, mutations that result in an increase in aggregation propensity tend to be purged out from the population, especially when they occur in a disordered context, since they are exposed to solvent, being this the reason that intrinsically disordered protein segments are in general, very soluble ( Santner et al, 2012 ; Uversky, 2013 , 2015 ; Graña-Montes et al, 2014 ). In this context, the inherent amyloid potential of Rho cPrD strongly suggests that this protein segment, and the surrounding predicted PrD, are conserved because they serve functional purposes in C. botulinum , in agreement with the general view that PrDs are important for protein–protein interactions and provide the flexibility required to self-organizing macromolecular assemblies in living cells ( Malinovska et al, 2013 ; Iglesias et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…We displayed an N-terminally truncated SUMO2 (herein referred to S2.WT) that lacks the first 14 unstructured residues (⌬N-14) including the primary site of SUMO chain formation (14). It was previously shown that the deletion of the unstructured N-terminal residues does not affect overall stability of SUMO2 (29). S2vs derived from such a library that additionally lack the C-terminal di-Gly motif (⌬GG) cannot be activated by the E1 complex or become a part of SUMO2/3 chains when expressed in cells.…”
Section: Library Design and Selection Of High Affinity Ubc9-binding Smentioning
confidence: 99%